Solve The Following Expression.

Asked by RACHIT_MAHAAN | 19th Sep, 2010, 01:08: PM

Expert Answer:

sin3x+cos2x=0sin3x=-cos2x3sinx-4sin3x = -(1-2sin2x)3sinx-4sin3x = -1+2sin2x4sin3x+2sin2x-3sinx-1=0This is a cubic equation. let a =sinx4a3+2a2-3a-1=0possible roots are -1 or 1a = -1 satisfies the equation(a+1)(4a2-2a-1)=0so a=-1  and on solving the quadratic,a = 2+208 or 2-208 =1+54 or a = 1-54But a=sinx , so sinx = -1,1+54,1-54">

Answered by  | 28th Sep, 2010, 11:58: AM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.